STATISTICAL PROCESSING OF BRAKE PADS WEAR PARAMETERS OF FREIGHT CARS - Ravlyuk, V. G.; Ravliuk, M. G.; Kirichenko, I. K. (Science and Transport Progress, 2020)
Purpose. This study is aimed at the statistical processing of the geometric parameters of pad wear of the modernized brake systems of freight cars` bogies. Methodology. A statistical approach to the construction of the graphical dependence of the brake pad wear on the car run was applied based on the previously collected wear data at checkpoints, which is regulated by the requirements of routine preventive repair. In this sense, theoretical and operational studies concerning the reduction of the non-standard wear of the brake pads were performed according to the regression analysis method based on the experimental data of the experimental operation of the upgraded devices of the brake systems of freight car bogies. The palliative approach to solution of this task is substantiated. Findings. It has been established that in practice there are cases when the pads do not provide their regulated run, as a result of which they are replaced prematurely for reasons of wedge-shaped wear. From the point of view of the economy and safety of their use, it leads to a decrease in brake efficiency in triangular brake systems. Experimental and scientific studies have found that when performing freight transportations plan, up to 95% of the car brake pads at standard braking devices have harmful double friction wear. This requires pads replacement in the warranty inter-repair period. It is established that during the inspection in the conditions of operation of brake shoe wear phenomena for the upgraded bogie devices based on the regression analysis, the prediction of the residual life of the pads was performed, the result of which is their use for the whole inter-repair period of freight cars. Originality. For the first time, the model of brake pad wear for upgraded devices of the bogie brake systems, depending on the car run, is adapted to build the regression dependence. Based on the results of the full-scale experiment, processing of the collected data on the pads wear in the absence of a normal law of statistical distribution was performed. Correspondence check of experimental and theoretical calculations according to the measurements of the pads wear was evaluated by Kochran’s test. A «palliative» approach is proposed for statistical analysis regarding the wear of pads in the operating conditions, allowing to predict the residual life of the brake pads for their use for the whole inter-repair period of freight wagons operation. Practical value. The results of the studies were tested on experimental rolling stock with upgraded devices for uniform wear of brake pads in the bogies. A patent for an invention was obtained, which is recommended for implementation during the design of new and modernization of the existing brake systems for freight car bogies.